Hypertension and Cognitive Decline in Rural Elderly Chinese - Gao, Sujuan (2009)
OBJECTIVES: To examine the association between hypertension and cognitive decline in older adults. DESIGN: Prospective observational study. SETTING: Four rural counties in China. PARTICIPANTS: Two thousand rural Chinese aged 65 and older (median age 70, range 65–92) participated in a baseline evaluation. A follow-up evaluation of 1,737 subjects was conducted 2.5 years after baseline. MEASUREMENTS: Cognitive function was assessed using the Community Screening Instrument for Dementia (CSID), Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) Word List Learning and Recall Tests, Indiana University (IU) Story Recall Test, Animal Fluency Test, and IU Token Test. Hypertension was defined as the mean of two readings of systolic blood pressure (BP) of 140 mmHg or greater, diastolic BP of 90 mmHg or greater, or according to self-report. Cognitive decline was derived as the difference between baseline and follow-up scores. Analysis of covariance models were used to estimate the association between hypertension, BP, and cognitive decline, adjusting for other covariates. RESULTS: Greater decline was found on the CERAD 10-Word List Learning (P<.001) and Recall (P =.01) scores for subjects with hypertension than for those without. In particular, significantly greater decline was seen in the group with hypertension that was not taking medication than in the group without hypertension. No significant difference on cognitive decline was found between subjects with hypertension who were taking medication and those without hypertention. CONCLUSION: Untreated hypertension was associated with greater cognitive decline in this Chinese cohort. Better hypertension detection and treatment in elderly people, especially in developing countries, may offer protection against cognitive decline